2017
DOI: 10.1194/jlr.m074260
|View full text |Cite
|
Sign up to set email alerts
|

Unbound free fatty acid profiles in human plasma and the unexpected absence of unbound palmitoleate

Abstract: We determined for the first time the profiles of the nine most abundant unbound FFAs (FFAus) in human plasma. Profiles were determined for a standard reference plasma of pooled healthy adults for which the Lipid MAPSMAPS Consortium had determined the total FFA profiles. Measurements were performed by using 20 different acrylodan-labeled fatty acid binding protein mutants (probes), which have complementary specificities for the nine FFAs that comprise more than 96% of long-chain plasma FFA. The acrylodan fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…FFA concentrations that elicit observed responses are around 100 nmol/L, which is typical for what is determined for unbound FFAs in the plasma (as opposed to millimolar concentration of albumin bound FFAs; ref. 48). In addition, a recent study, targeting the fatty acid receptor CD36 showed that metastasis-initiating cells rely on free fatty acids to promote metastasis (49).…”
Section: Discussionmentioning
confidence: 99%
“…FFA concentrations that elicit observed responses are around 100 nmol/L, which is typical for what is determined for unbound FFAs in the plasma (as opposed to millimolar concentration of albumin bound FFAs; ref. 48). In addition, a recent study, targeting the fatty acid receptor CD36 showed that metastasis-initiating cells rely on free fatty acids to promote metastasis (49).…”
Section: Discussionmentioning
confidence: 99%
“…non-protein bound) concentration of FAs in blood [87]. The concentration of unbound FAs was found to be 7.5 + 2.5 nM in humans [88] and increases exponentially with a rise in the total plasma FA concentration [89]. Unfortunately, no studies report on kinetics of hepatic FA uptake in humans, thus a comparison of the plasma (unbound) FA concentration to the K M value of hepatic FA uptake is not possible at present.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these epidemiologic studies are obscured by various forms and sources of palmitoleate present in the serum. In addition, palmitoleate may exist almost exclusively in an inactive, protein-bound form, so the level of bioactive palmitoleate may not correlate with serum levels [32]. Further research is necessary to characterize how much the adipose tissue contributes to circulating palmitoleate and its role in human metabolic health.…”
Section: Palmitoleic Acidmentioning
confidence: 97%